The Awarness of Legal Violations of Underage Motorcycle Riders Among Students of SMPN 2 Buduran, Sidoarjo - Loladestyn, Rahma Remade; Omar, Habibah (Journal of Southern Sociological Studies, 2025)
This research aims to explore how the level of legal awareness of underage motorists among students of SMPN 2 Buduran, Sidoarjo. The method used in this research is by conducting observations, interviews, and documentation as data collection. The subjects in this study are students of SMPN 2 Buduran, Sidoarjo who currently go to school using motorized vehicles or who have experience riding motorcycles. In this study, the data analysis used includes data reduction, data presentation, and conclusion making, namely interactive data analysis techniques. As well as using the theory of rational action by max webber with a qualitative approach. The results showed that the majority of SMPN 2 Buduran, Sidoarjo students who rode underage motorbikes had a fairly high level of awareness of law violations. This research provides a deeper understanding of the legal awareness of SMPN 2 Buduran, Sidoarjo students in driving and can be the basis for related parties to develop more effective education and socialization that is useful for increasing their awareness of law violations in traffic, especially for underage motorcyclists.